Responses of neurons in the ferret superior colliculus to the spatial location of tonal stimuli. - King, A; Carlile, S (1994)
Using multi-unit recordings, we compared the azimuthal spatial selectivity of auditory neurons in the deep layers of the ferret superior colliculus (SC) to broadband and tonal stimuli. Responses to noise were tuned at different sound levels to a single location, which varied topographically along the rostrocaudal axis of the nucleus to form a map of sound azimuth. Frequency response profiles tended to be multi-peaked, so the spatial tuning was examined at two or more frequencies in each case. Some of the azimuthal response profiles obtained with tonal stimuli were bilobed, as expected from the spatially ambiguous cues available at individual frequencies, although the rest were tuned to a single region of space. The preferred sound directions usually varied with the frequency used, and the range of auditory best positions at each recording site was significantly greater with tones than with noise. Comparison with the acoustical properties of the auditory periphery suggested that the near-threshold positional selectivity of many of the tonal responses may be determined by the monaural directionality of the outer ear. When the sound level was raised by 20 dB so that both ears were stimulated at all speaker locations, the range of tonal best positions obtained at each frequency increased and some of the units responded best to pure tones located in the ipsilateral hemifield. The lack of topographic order in the distribution of tonal spatial selectivity along the rostrocaudal axis of the SC indicates the need for a broadband input, incorporating the spectral localization cues provided by the outer ear, in the construction of a neural map of auditory space.